2021
DOI: 10.1080/15685551.2021.1935014
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Carborane Modified Liquid Fluoroelastomers and the investigation of their properties

Abstract: The preparation of liquid fluoroelastomers that are liquid with excellent mechanical properties remains a challenge. Here, we show a very straightforward method to produce liquid fluoroelastomers by introducing carborane. Carborane-terminated liquid fluoropolymer was synthesized by Steglich reaction of carboxyl-terminated liquid fluoropolymer and 1,7-bis (hydroxy)-carborane. The product is brown, viscous at room temperature and in the semi-solid state. On this basis, HDI Trimer was used as a curing agent to cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…Our research team has been extensively studied the mechanisms of degradation of LTCFs made with CH-assisted oxidative degradation. It was found that Zaitsev’s rule was mostly followed, and Hofmann’s rule was partially followed during the dehydrofluorination of the P(VDF-HFP) copolymer. , However, more practical and theoretical research is needed to determine if the degradation mechanism still holds under the novel volumetric heating circumstances of MW.…”
Section: Introductionmentioning
confidence: 99%
“…Our research team has been extensively studied the mechanisms of degradation of LTCFs made with CH-assisted oxidative degradation. It was found that Zaitsev’s rule was mostly followed, and Hofmann’s rule was partially followed during the dehydrofluorination of the P(VDF-HFP) copolymer. , However, more practical and theoretical research is needed to determine if the degradation mechanism still holds under the novel volumetric heating circumstances of MW.…”
Section: Introductionmentioning
confidence: 99%
“…Carborane and its derivatives are highly sought after due to their 3D-aromatic structure and have been investigated to improve the heat stability of organic polymers. Carborane is soluble in commonly used organic solvents and can be easily introduced into polymer systems such as polyester, , polysiloxane, , polyamides/polyimides, polyphosphazenes, heteroelement-substituted polymers, , and so on. Among the polymers discussed above, polysiloxane stands out because the introduction of carborane segments substantially improves its heat resistance. The addition of carborane segments significantly improved the modified polymers’ thermal resistance.…”
Section: Introductionmentioning
confidence: 99%